Peningkatan Pemahaman Tentang Lembaga Lembaga Negara Pada Mata Pelajaran PKn Melalui Metode Diskusi Kelompok Siswa Kelas IV SD. Negeri 008 Rambah Hilir Tahun Pelajaran 2016/2017 - Nurjanah Nurjanah (STKIP Rokania Pasir Pangaraian, 2018)
Abstract, This classroom action research was conducted at SDN 008 Rambah Hilir in class IV. This study aims to improve the understanding of state institutions on Civics subjects through group discussion methods. Based on the data collected by researchers from the implementation of learning cycle I and cycle II, researchers draw some conclusions are: Improved learning outcomes of students class IV SDN 008 Rambah Hilir there are subjects of Civics in understanding the institutions of state at the central level has been achieved, in cycle II 88,71% (90%) Criterion A compared to cycle I 62, (62%) Criteria C. The application of varied learning method and the use of visual aids is very effective for the achievement of learning objectives to be achieved